问题 解答题
2
5
×[
3
5
÷(
3
5
+
9
25
)]
=
[25+(
1
3
+
1
4
)]×4
=
10
11
÷(2-
5
3
2
5
=
1
7
÷[5×(
3
5
-
2
5
)]
=
[1-(
1
4
+
3
8
)]÷
3
4
=
[
9
16
+0÷(
1
7
+
7
8
)]×
4
3
=
答案

(1)

2
5
×[
3
5
÷(
3
5
+
9
25
)],

=

2
5
×[
3
5
÷
24
25
],

=

2
5
×
5
8

=

1
4

(2)[25+(

1
3
+
1
4
)]×4,

=[25+

7
12
]×4,

=25×4+

7
12
×4,

=100+

7
3

=102

1
3

(3)

10
11
÷(2-
5
3
2
5

=

10
11
÷
1
3
×
2
5

=

30
11
×
2
5

=

12
11

(4)

1
7
÷[5×(
3
5
-
2
5
)],

=

1
7
÷[5×
1
5
],

=

1
7
÷1,

=

1
7

(5)[1-(

1
4
+
3
8
)]÷
3
4

=[1-

5
8
3
4

=

3
8
÷
3
4

=

1
2

(6)[

9
16
+0÷(
1
7
+
7
8
)]×
4
3

=[

9
16
+0]×
4
3

=

9
16
×
4
3

=

3
4

单项选择题
单项选择题 A1型题